2017
DOI: 10.3389/fevo.2017.00063
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal in the Urban Matrix: Assessing the Influence of Landscape Permeability on the Settlement Patterns of Breeding Songbirds

Abstract: The ability of organisms to disperse across urban landscapes is theorized to be constrained by habitat fragmentation. While previous research has shown the distribution of forest patches is a determinant of dispersal patterns among forest-obligate bird species, the impacts of habitat distribution on the dispersal of "urban-adapted" species, has yet to be examined. Here, we use capture-reencounter data of birds banded over a 9-year period at six banding stations in greater Washington, DC to assess dispersal in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 74 publications
2
14
0
Order By: Relevance
“…Five weighted resistant maps were produced, each corresponding to a different sized sliding window: 15, 25, 35, 55 and 75 m in diameter. This range is consistent with the perceptual range of our biological models (for moths, we used butterflies as proxy: Merckx & Van Dyck, 2007; Pe'er et al, 2004; passerines: Evans et al., 2017).…”
Section: Methodssupporting
confidence: 81%
“…Five weighted resistant maps were produced, each corresponding to a different sized sliding window: 15, 25, 35, 55 and 75 m in diameter. This range is consistent with the perceptual range of our biological models (for moths, we used butterflies as proxy: Merckx & Van Dyck, 2007; Pe'er et al, 2004; passerines: Evans et al., 2017).…”
Section: Methodssupporting
confidence: 81%
“…2013, Evans et al. 2017). These two variables were derived from national maps of land cover surface for the conterminous United States in 2011 at 30 m 2 resolution as part of the National Land Cover Data (NLCD) set (Homer et al.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to loss of habitat, other negative effects of impervious surfaces (e.g., roads, pavement, buildings) include road noise (Goodwin andShriver 2010, Klingbeil et al 2020), higher pollution (Roux and Marra 2007), and more artificial light (Ciach and Fr öhlich 2017). Impervious surface may also fragment habitat and limit dispersal, even with the presence of an intact mature canopy, because of anthropogenic mortality hazards (Evans et al 2017, Adalsteinsson et al 2018. The negative effects of impervious surface (and of urbanization as a whole) may not be fully mitigated by increases in tree canopies alone.…”
Section: Neighborhood-scale Featuresmentioning
confidence: 99%
“…Additionally, it has been recently shown that differences can likely arise when using different estimators of home range size [ 69 ]. Moreover, both simulation-based [ 87 ], and empirical studies have demonstrated support for how differences in landscape permeability within urban areas can influence bird movement [ 88 – 90 ].…”
Section: Discussionmentioning
confidence: 99%